An Analysis Of Metaphors On Natural Advertisement - Rajagukguk, Fratiwi Juita; Sidabutar, Usman; Napitupulu, Fenty Debora (Lembaga Riset dan Inovasi Almatani, 2024)
This thesis discusses the analysis of metaphors contained on natural advertisements. The purpose of this research is to classify the types of metaphors contained on natural advertisements and find the most dominant metaphor on the advertisements. This research was conducted using qualitative method. The author reads and understands the contents of the advertisements that consist of 10 advertisements to obtain data. The data collection instrument is observation. The data is obtained from advertisement whose topics are about nature. The author found 114 data on natural advertisements. The types of metaphors contained on natural advertisements are representatives consisting of concretive metaphor 64 data, animistic metaphor 2 data, humanizing metaphor 45 data, and synaesthetic metaphor 3 data. From the research, the author concludes that concretive metaphor is the most dominant and frequently used in natural advertisements. The benefits of this research for the state and nation, especially for students and English teachers are that this research can be used as a source of teaching material, a source of students in learning more about metaphor, and for further authors, especially in linguistic that analyze one-way objects such as advertisements, art like poems, drama, and songs.